Landscape-based nutrient application in wheat and teff mixed farming systems of Ethiopia: farmer and extension agent demand driven approach - Desta, Gizaw; Legesse, Gizachew; Agegnehu, Getachew; Tigabie, Abiro; Nagaraji, Satish; Gashaw, Tadesse; Degefu, Tulu; Ayalew, Baye; Addis, Ayalew; Getachew, Tsegaye; Managido, Demis; Bazie, Zerfu; et al. (Frontiers in Sustainable Food Systems, 2023)
Adapting fertilizer use is crucial if smallholder agroecosystems are to attain the sustainable development goals of zero hunger and agroecosystem resilience. Poor soil health and nutrient variability characterize the smallholder farming systems. However, the current research at the field scales scale does not account for nutrient variability across landscape positions, posing significant challenges for targeted nutrient management interventions. The purpose of this research was to create a demand-driven and codevelopment approach for diagnosing farmer nutrient management practices and determining landscape specificlandscape-specific (hillslope, mid slopemid-slope, and foot slope) fertilizer applications for teff and wheat. A landscape segmentation approach was aimed to address gaps in farm-scale nutrient management research as well as the limitations of blanket recommendations to meet local nutrient requirements. This approach incorporates the concept of interconnected socio-technical systems as well as the concepts and procedures of co-development. A smart mobile app was used by extension agents to generate crop-specific decision rules at the landscape scale and forward the specific fertilizer applications to target farmers through SMS messages or print formats. The findings reveal that farmers apply more fertilizer to hillslopes and less to mid-and foot slopes. However, landscape-specific fertilizer application guided by crop-specific decision rules via mobile applications resulted in much higher yield agronomic improvements, 23% and 56% at foot slopes and 21% and 6.5% at mid slopes for wheat and teff, respectively.